A qualitative investigation of unsupervised outdoor activities for 10- to 13-year-old children: "I like adventuring but I don't like adventuring without being careful". (August 2020) - Brussoni, Mariana; Lin, Yingyi; Han, Christina; Janssen, Ian; Schuurman, Nadine; Boyes, Randy; Swanlund, David; Mâsse, Louise C.
Abstract: There has been increasing recognition of the importance of children's outdoor play and independent mobility for thriving children, neighbourhoods, cities and society, which has led to calls to reverse children's retreat from the street commonplace in many Western nations. We privilege the voices of children aged 10–13 living in three diverse neighbourhoods in an urban centre in Canada to examine the factors that influence children's unsupervised outdoor activities (UOA), such as play, hanging out, and active. A total of 105 children participated in go-along interviews. Analyses revealed two themes: First, 'feeling safe' encompassed a sense of social and physical safety, including children's sense of neighbourliness, social dangers, discomfort around traffic, and personal agency to keep themselves safe. Second, having 'things to do, ' included the affordances that children perceived as important in their neighbourhoods, particularly having other children to play with, diverse amenities and access to nature, and opportunities for challenge and risky play. We outline a conceptual model of children's decision process for UOA that identifies key variables that influence children's engagement in UOA. Highlights: Unsupervised outdoor activities (UOA) are key for thriving children and societies. Children identified feeling safe and having things to do as necessary for UOA. Neighbourliness, other children, and personal agency helped children feel safe. Children wanted friends to hang out with and things to do within walking distance. Fostering neighbourliness and including children's voices in planning are important.